Clan Criminality and the Fight against Organized Crime in Germany (Rivista di Studi e Ricerche sulla criminalità organizzata, 2021)
This paper aims at critically analysing the phenomenon of Clankriminalität in Germany and the institutional responses adopted towards this and other forms of organized crime operating on the German territory. This form of organised crime will be examined in light of the broader discussion on migration and so-called parallel societies, which has characterised the public and scientific debate of the last 20 years.
Keywords: Clan Criminality; parallel justice; immigration; honor; mafia